2024
DOI: 10.26434/chemrxiv-2024-jcjgd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ru(II)–Pd(II) dinuclear complexes of di(pyridin-2-yl)amino-substituted 1,10-phenanthrolines: synthesis, characterization and application for catalysis

Violetta A. Ionova,
Alena V. Dmitrieva,
Anton S. Abel
et al.

Abstract: Dinuclear complexes bearing Ru(II) photoactive center are of interest for the development of efficient dual catalysts for many photocatalyzed reactions. Ditopic polypyrine ligands – bis(pyridine-2-yl)amino-1,10-phenanthrolines – containing additional coordination site (bis(pyridine-2-yl)amine, dpa) at positions 3, 4 or 5 of 1,10-phenanthroline core (Phen-3NPy2, Phen-4NPy2 and Phen-5NPy2) were synthesized. They were used as bridging ligands to obtain dinuclear complexes of composition [(bpy)2Ru(Phen-NPy2)PdCl2]… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The coordination mode was supported by the NMR spectroscopy (Figures S7-S10) and briefly discussed in the Supporting Information. [16] The extinction coefficients of the complexes in the visible region of the spectrum do not differ significantly from those of standard photocatalysts based on Ru(II) or Ir(III) (Figure S11, Table S6). The Ni complexation does not lead to significant change in UV-vis spectrum and emission quenching (Figure S12).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The coordination mode was supported by the NMR spectroscopy (Figures S7-S10) and briefly discussed in the Supporting Information. [16] The extinction coefficients of the complexes in the visible region of the spectrum do not differ significantly from those of standard photocatalysts based on Ru(II) or Ir(III) (Figure S11, Table S6). The Ni complexation does not lead to significant change in UV-vis spectrum and emission quenching (Figure S12).…”
Section: Resultsmentioning
confidence: 92%
“…[10,15] We have previously shown that the bonding of Ru(II) and Pd(II) using ditopic ligand based on 1,10-phenanthroline and di(pyridin-2yl)amine leads to a significant increase of the efficiency of such photoactivated precatalysts in Cufree Sonogashira coupling compared to a mixed system. [16] It is worth noting that no examples of the use of binuclear complexes in the reaction between aryl halides and sodium arylsulfinates under visible light have been described in the literature.…”
Section: Introductionmentioning
confidence: 99%